The role of strategic leadership in Coega Development Corporation: a case study - Davids, Mogamad Sadiek (Rhodes University, Faculty of Commerce, Investec Business School, 2010)
South Africa became a democracy after its election in April 1994. Thereafter, the country faced the daunting task of trying to fast-track economic growth and addressing social challenges. The Department of Trade and Industry was mandated by the newly elected government to spearhead economic development in order to address these challenges. Trade policy instruments such as industrial development zones formed part of government's strategic economic instruments to achieve economic reform. The Coega Industrial Development Zone (CIDZ) near Port Elizabeth was one of many economic development zones created principally to promote export orientated manufacturing. The Coega Development Corporation (CDC) was registered as a company to develop, operate and manage the CIDZ. The literature suggests that strategic leadership is important for organizational success. Strategic leadership is described as the ability to influence others to make day-to-day voluntary decisions that enhance long-term viability while maintaining short term financial stability. Literature further suggests that strategic leaders deal with the evolution of organizations and their changing aims and transform them through their capabilities and strategic leadership roles such as being a figurehead, spokesperson, team builder, design school planner and so on. The aim of this research is to analyse the role of strategic leadership with the objectives to ascertain whether strategic leadership contributed to the success of the development of CDC, and identify possible challenges they are confronted with in the execution of their leadership duties. This research was conducted from an interpretivist perspective as the researcher attempted to develop insight into how the strategic leadership of CDC viewed and understood their role. The strategic leadership of CDC, who were the focus of this study, consisted of the executive management team of the organization, including the Chief Executive Officer (CEO). The research design was in the form of a case study of the CDC leadership, with data collected through semi-structured interviews and documents. The most prominent roles exercised by the leadership of CDC included creating a vision and strategy development and inculcating a teamwork corporate culture. Other roles identified include that of team builder, fostering innovation and developing human capital etc. A lack of stakeholder management as well as managing the culture of the organization as it expands and grows, remain critical challenges. Finally recommendations are made together with suggestions for future research.
Keywords: Coega Development Corporation; Industrial development projects -- South Africa -- Eastern Cape -- Case studies; Leadership -- South Africa -- Eastern Cape -- Case studies; Strategic planning -- South Africa -- Eastern Cape -- Case studies; Organizational behavior -- South Africa -- Eastern Cape -- Case studies